Determination of DNA content and relative 2C genome sizes of some promising commercial varieties of sugarcane using flow cytometer - S.K. Ghosal, A. Mondal; Kalyan Kumar De, T. Pal (Current Botany, 2017)
In the present study, 2C DNA content and the genome sizes (in picograms-pg and megabase pairs-Mbp respectively) of 19 promising commercial varieties of sugarcane, the derivatives of man-made interspecific hybrids between cultivated and wild species were analyzed using flow cytometry. In this work, 2C nuclear DNA content was determined. Knowing the 2C nuclear DNA content, the unknown chromosome numbers of the varieties could be predicted. Large differences (65 % variation) in DNA content (2C) of 19 varieties were detected, ranging, from 3.80 pg to 10.96 pg, which corresponds to a genome size ranging from 3724.00 Mbp to 10740.80 Mbp due to the variation of ploidy level and are considered the most complex genomes among crop plants. However, the relationship between chromosome number and genome size was highly significant (P < 0.001). In the present study, internode diameter, Sugar juice content and cane yield/ha are also positively correlated with DNA content. The estimated genome sizes would also yield information critical for sugarcane breeding and genome sequencing programs. Keywords: Genome size, Sugarcane varieties, Flow cytometry, DNA content.